Evaluation of the Occupational Health and Safety (K3) Management System in the Construction Project of the Campus Building of Pamulang University - Agung Suciyanto; Deva Robbie Willian; Rafqi Danial Farabi; Awliya Tribhuana (Journal of World Science, 2026)
The construction industry has a high level of occupational accident risk, making the implementation of an Occupational Safety and Health Management System (OSHMS) essential in construction projects. This study aims to evaluate the implementation of OSHMS in the construction project of the Pamulang University Campus Building and to identify potential hazards, risk levels, and risk control measures applied on site. This research employed a quantitative descriptive method, collecting data through field observations, interviews, and questionnaires distributed to 55 respondents directly involved in the project. Data analysis was conducted using SPSS to test the validity and reliability of the questionnaire, while the HIRARC method was used for hazard identification, risk assessment, and risk control. The results indicate that all questionnaire items were valid and reliable, with Cronbach’s Alpha values of 0.842 for the likelihood variable and 0.818 for the severity variable. The evaluation of OSHMS implementation achieved an average score of 4.07, categorized as good. The highest risk was identified in upper structural work, particularly the hazard of falling from height. It can be concluded that the implementation of OSHMS in the project has been carried out effectively; however, improvements in supervision and worker compliance are still required to further reduce occupational accident risks